THE INFLUENCE OF SMASH EXERCISE USING HANGER BALL ON THE ACCURACY OF SMASH OPEN IN THE VOLLEY BALL GAME IN CLASS VIII PRINCESS STUDENTS OF SMP NEGERI 50 PALEMBANG - Siti Ayu Risma Putri (Program Pascasarjana Universitas Negeri Jakarta, 2019)
​This research is entitled 'The Effect of Smash Training Using Hanging Ball Against the Accuracy of Smash Open in Volleyball Games in Girls' Class VIII Students in Palembang 50 Public Middle School'. This study is an experimental study, with a population of VIII grade female students totaling 120 people, using a random sampling technique the sample was taken 50% of the population to be 60 female students. Through the ordinal hearing system, students are divided into two groups of 30 students into an experimental group that is treated and 30 students as a control group that is not treated. The instrument used for the skills test is the smash open. The smash open test passes through the field net that has been scored. Data collection techniques in this study used the 't' test. T test obtained from this study tcount = 15.42 while t (0.95) (60) = 1.771 is t obtained from the distribution table, obtained tcount = 43.87 ≥ table (1-α) = 31.47. It can be concluded that there is a significant difference between the experimental group and the control group, then the hypothesis that reads,